LEARNING STRATEGY FOR THE “KINANTHI” MACAPAT SONG IN SERAT WEDHATAMA AT RANDUDONGKAL STATE HIGH SCHOOL - Hikmah, Paojiatul; Gandung Joko Srimoko (Jurnal Penelitian Musik, 2025)
Each level of education in Central Java has local content in the form of Javanese language subjects including SMANegeri 1 Randudongkal, divided into several materials in it, one of which is learning the tembang macapat kinanthi in wedhatama fiber. The learning of the macapat song, especially the kinanthi song, has several obstacles in theimplementation of learning both from educators and students. The purpose of this study was to determine the learning strategy of the "kinanthi" macapat song at SMA Negeri 1 Randudongkal, Pemalang district, Central Java. The research method used is a qualitative research method with a descriptive qualitative approach. The research was conducted in Randudongkal, Pemalang district, Central Java province. The object of this research is the macapat tembang learning method at SMA N 1 Randudongkal. The data contained is the result of literature study, interviews, observations, anddocumentation. The result of this research is that the learning of macapat song in SMA N 1 Randudongkal uses participative teaching and learning strategies. This participatory learning involves the main actors, namely teachers (teachers) and learning residents, namely students from the beginning of planning, implementation and evaluation